2017
DOI: 10.1002/aenm.201602349
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transfer from Methylammonium Lead Iodide Perovskite to Organic Transport Materials: Efficiencies, Transfer Rates, and Interfacial Recombination

Abstract: IntroductionSolar cells employing metal halide perovskites as light absorbers have undergone a tremendous development over the past years, resulting in photovoltaic devices with record efficiencies exceeding 22%. [1][2][3] The impressive progress in device efficiency is mainly due to (i) optimizing experimental procedures to obtain perovskite materials with improved crystallinity, (ii) adjusting the perovskite composition, and (iii) investigating different transport materials. However, it remains a major Perov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
170
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 120 publications
(181 citation statements)
references
References 30 publications
(55 reference statements)
8
170
3
Order By: Relevance
“…Recent work by Huang and co-workers indicated that thermal annealing of [60]PCBM could passivate traps in the perovskite film. [23] In our case, the thermal treatment of [24,25] The extent of the PL quenching by all the EELs is similar at high and low temperature, showing that the electron transfer occurs with similar efficiency at different temperatures. At low temperature, the enhanced PL emission of the perovskite layer is an indication of higher band-to-band recombination of the free electrons and holes, lower nonradiative recombination due to the deactivated traps and lower photon scattering ( Figure S10, Supporting Information).…”
Section: Resultsmentioning
confidence: 88%
“…Recent work by Huang and co-workers indicated that thermal annealing of [60]PCBM could passivate traps in the perovskite film. [23] In our case, the thermal treatment of [24,25] The extent of the PL quenching by all the EELs is similar at high and low temperature, showing that the electron transfer occurs with similar efficiency at different temperatures. At low temperature, the enhanced PL emission of the perovskite layer is an indication of higher band-to-band recombination of the free electrons and holes, lower nonradiative recombination due to the deactivated traps and lower photon scattering ( Figure S10, Supporting Information).…”
Section: Resultsmentioning
confidence: 88%
“…[ 10 ] As with many emerging photovoltaic technologies, a major focus of the research community has been trying to understand the origin of open‐circuit voltage losses and a range of different measurement techniques have been proposed to decouple, for example, the contribution of interfacial and bulk recombination on the V OC of the cell. [ 11–19 ] These include electrical [ 19 ] and all‐optical transient measurements such as pump‐probe techniques [ 14–16,20,21 ] ; moreover all‐electrical measurements, for example, impedance spectroscopy [ 15,17,20–22 ] and optical measurements in steady‐state such as photoluminescence spectroscopy. [ 11–13 ] Other attempts have been made to explain the dominant recombination mechanism via the ideality factor ( n ID ) of the complete cell, [ 11,23–26 ] however with somewhat limited success considering the difficulty of describing multiple parallel recombination processes in a cell by a single parameter.…”
Section: Figurementioning
confidence: 99%
“…In most of the mentioned reports the injection is observed indirectly by monitoring changes of the TAS signals characteristic for the perovskite layer. The temporal evolution of these signals can be influenced by additional factors, such as film quality and morphology or interfacial recombination . Direct observation of charge carrier injection by detecting spectral signatures caused by the injected carriers in the adjacent contact material is therefore highly desirable.…”
Section: Introductionmentioning
confidence: 99%